Improved Electrochemical Oxidation of Polyalcohols in Alkaline Media on Palladium‐Nickel Catalysts. Issue 29 (12th October 2017) - Muneeb, Omar; Estrada, Jose; Tran, Timothy; Hu, Shuozhen; Khorasani, Bita; Fry‐Petit, Allyson; Scudiero, Louis; Ha, Su; Haan, John L.
Abstract: Palladium is an efficient monoatomic catalyst for the electrochemical oxidation of polyalcohols in alkaline media, yet the oxidation rate is still slow compared to other smaller molecules. In order to improve the oxidation rate, Ni was mixed with Pd for synthesis of PdNi/C nanoparticles. The oxidation rates of ethylene glycol (EG), propylene glycol (PG), and glycerol (G) on Pd/C were compared to the oxidation rates on Pd16 Ni84 /C, Pd53 Ni47 /C, and Pd68 Ni32 /C. The oxidation rate of PG was enhanced by the presence of Ni as much as 14 times (Pd53 Ni47 /C). The oxidation rate of EG was enhanced 2.3 times on Pd68 Ni32 /C, and G was improved 2.9 times on Pd53 Ni47 /C. A significant shift in d‐band center was also observed (as high as +0.11 eV in Pd53 Ni47 /C) on each PdNi/C catalyst compared to that of Pd/C due to the presence of Ni. The correlation between increased oxidation rate and shift in d‐band center is indicative of the presence of an electronic effect, which is particularly strong for PG. Abstract : The electrochemical oxidation rate of propylene glycol on Pd53 Ni47 /C is more than 13 times greater than on Pd/C after 3 hours due to a 0.12 eV upshift in d‐band center. A linear relationship between d‐band center and oxidation rate was observed for various Pd/C and PdNi/C catalysts. Other polyalcohols (glycerol and ethylene glycol) exhibit improved oxidation rate, as well, when Ni is added to Pd.